Meneliti Pendorong Perilaku Menabung di Kalangan Pengusaha Perempuan di Nigeria - Ademola, Abimbola; Kazeem, Bayo; Oladejo, Titilayo M (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Savings behavior among women entrepreneurs is a crucial factor in fostering financial independence and business sustainability. Therefore, this study examined the drivers of savings behavior among women entrepreneurs in Oyo State, Nigeria, Specifically, the influence of socio-economic variables, availability of financial services, and cultural and societal norms on the saving behavior of women entrepreneurs was investigated. Using a sample size of 240 respondents, data were collected through structured questionnaires and interviews, then analyzed using descriptive statistics and regression analysis. The results showed that socio-economic factors like age, education, income, and years of experience positively reinforce saving behavior, while larger household size negatively affects the ability to save. Besides, access to financial services-driven by proximity to institutions of finance, availability of financial products and interest rates, financial literacy programs, use of digital financial services-emerged as a critical driver of saving behavior. These results further indicated that savings decisions are highly influenced by cultural expectations, family influence, and religious belief, revealing that policy intervention in the financial inclusion of women as entrepreneurs must not just consider the economic factors but also the cultural and social contexts. The study further recommends the implementation of financial literacy programs for women entrepreneurs, the development of accessible financial products by institutions, and community-based initiatives for changing positive cultural narratives concerning women's financial independence.